Budaya Organisasi dan Kepuasan Kerja: Kinerja sebagai Variabel Mediasi: Organizational Culture and Job Satisfaction: Performance as a Mediation Variable - Muhammad Thahrim Imam; Zulkifli Zulkifli; Irfandi Buamonabot (Society, 2022)
Research has been considered “negligent” in seeing performance as mediation on the relationship between organizational culture and job satisfaction, even more so in village governance. The study aimed to test performance directly related to the relationship between organizational culture and job satisfaction. This research was conducted in South Halmahera Regency, North Maluku Province. The total population in this study was 249 people, and samples were conducted by the purposive sampling method. A total of 179 respondents were involved in the survey. The validity and reliability test uses factor analysis with factor loading values ? 0.5 and Cronbach alpha ? 0.7. Simple regression and hierarchical analysis are used to test research hypotheses. The results showed that the performance variables were as complete as mediation in the study.